2021
DOI: 10.3389/fphar.2021.617559
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Efficacy and Mechanisms of Traditional Chinese Medicines as a Therapeutic Option for Ionizing Radiation Induced Damage

Abstract: Ionizing radiation damage refers to acute, delayed, or chronic tissue damage associated with ionizing radiation. Specific or effective therapeutic options for systemic injuries induced by ionizing radiation have not been developed. Studies have shown that Chinese herbal Medicine or Chinese Herbal Prescription exhibit preventive properties against radiation damage. These medicines inhibit tissue injuries and promote repair with very minimal side effects. This study reviews traditional Chinese herbal medicines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 179 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…Till now, testicular injury after IR exposure has no specific or effective modalities [ 9 ]. Studies showed that antioxidants exhibited therapy for radiation damage based on radiation-induced oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Till now, testicular injury after IR exposure has no specific or effective modalities [ 9 ]. Studies showed that antioxidants exhibited therapy for radiation damage based on radiation-induced oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is urgent to develop radioprotective drugs with low side effects. Many Traditional Chinese Medicine can improve radiationinduced damage [155]. The neuroprotective effect of LBP has been reported in both in vivo and in-vitro models [43].…”
Section: Discussionmentioning
confidence: 99%
“…These free radicals cause approximately 70% of the IR-induced injuries and lead to a constant state of oxidative stress in the organism. 16,17,20 Oxidative damage is the main mechanism underlying the sustained injury induced by IR exposure. 18 Cellular damage is accompanied by the induction of inflammatory responses, increased immunoreactivity, and the activation of other signaling pathways that ultimately cause apoptosis and other forms of cell death, while accelerating cellular senescence.…”
Section: The Mechanism Of Ir-induced Injurymentioning
confidence: 99%
“…Some Chinese herbal prescriptions and medicines exhibit properties that could prevent against radiation injury with minimal side effects by promoting tissue recovery and inhibiting tissue damage. 20 Chinese herbal prescriptions contain active ingredients capable of preventing free-radical damage, mitigating DNA damage, decreasing apoptosis, and stimulating repair mechanisms after tissue injury. Many traditional Chinese medicines have been found to significantly decrease the mortality rate of mice exposed to TBI at lethal doses.…”
Section: Chinese Herbal Medicinesmentioning
confidence: 99%
See 1 more Smart Citation